How the Evolution and Track of Several Digital Technologies in Science Education? - Nisa', Khoirun; Indriana Safitri, Afaurina; Mubarok, Husni (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Objective:  Digital technologies have significantly impacted science education. This research uses a bibliometric analysis to analyze the evolution of various digital technologies in science education. Method: The research uses the PRISMA method to conduct a systematic review using the Scopus database. Results: LMS was the highest publication and citation in the last five years. DL and LMS publications increased, but DA decreased. DL, LMS, DA, and EA publications dominate article papers. SC and ILS dominated conference papers. 57% of DT researchers are European, with 19% from Asian and North American researchers. Twenty-four sources are participating in DT research. Many universities in America, such as Harvard University, Stanford University, MIT, and Berkeley University, the University of California have extensive facilities for participating in DL, LMS, DA, EA, SC, and ILS research. Novelty: This research is essential to educators, researchers, and policymakers to provide insights on improving digital teaching technologies, inform policy, and promote interdisciplinary collaboration. It also offers an overview and research trend of DT in science education research and its opportunities for researchers, librarians, digital developers, educators, and policymakers to develop further research, education, and technology. Further research can be conducted based on the scope of mathematics or physics education, especially to investigate specific skills or STEAM.